2017
DOI: 10.1002/rmv.1929
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E and pregnancy: current state

Abstract: Hepatitis E virus (HEV) is responsible for more than 50% of acute viral hepatitis cases in endemic countries. Approximately 2 billion individuals live in hepatitis E-endemic areas and, therefore, are at risk of infection. According to World Health Organization, HEV causes about 20.1 million infections and 70 000 deaths every year. In developing countries with poor sanitation, this disease is transmitted through contaminated water and is associated with large outbreaks, affecting hundreds or thousands of people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
162
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(175 citation statements)
references
References 85 publications
0
162
0
2
Order By: Relevance
“…Several studies from highly endemic areas have shown high mortality rate in pregnant women who develop acute hepatitis E (up to 30% and especially in the third trimester) . The high mortality rate in pregnancy have not been reported in patients infected with genotypes 3 and 4 .…”
Section: Discussionmentioning
confidence: 98%
“…Several studies from highly endemic areas have shown high mortality rate in pregnant women who develop acute hepatitis E (up to 30% and especially in the third trimester) . The high mortality rate in pregnancy have not been reported in patients infected with genotypes 3 and 4 .…”
Section: Discussionmentioning
confidence: 98%
“…The reason being that acute HEV in pregnancy can progress to fulminant hepatitis with a high mortality rate, especially, if it occurs in the 3rd trimester [17,51]. Further, reports have shown that HEV infection during pregnancy can lead to maternal mortality rate of 15% to 25%, especially, with genotype 1, which together with genotype 2 are prevalent in the developing countries [52].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence is increased in the second and third trimester as compared to the first trimester. Mortality has been estimated at 25-30% in pregnant women [29]. The mechanisms underlying the increased susceptibility of pregnant women to hepatitis E infection and not to other hepatitis viruses is not clear.…”
Section: Hepatitis Ementioning
confidence: 99%